PENGARUH KENAIKAN LABA BERSIH PERUSAHAAN TERHADAP TIMING PENYAMPAIAN LAPORAN KEUANGAN TAHUNAN PERUSAHAAN (Studi empiris pada perusahaan LQ-45 di Indonesia yang terdaftar pada Bursa Efek Indonesia tahun 2017) - Ahmad HIjri Alfian; Mukhlas Adi Putra (JURNAL STIE SEMARANG, 2019)
The purpose of this study is to verify the increase in the company's net profit on the timing of submission of the company's financial statements on the Indonesian stock exchange. This study also has another purpose, namely to assess the influence of existing stakeholder theory which assumes that the company has a responsibility to report the condition of the company to the company's stakeholders. Companies that experience an increase in net income should report their financial statements faster than the specified time, 30 April of the previous year, to make it easier for stakeholders to make decisions.The sample of this study is 42 companies that entered the LQ-45 registered in the Indonesian Stock Exchange in the period of 2017. While the analytical method used to examine the effect of the effect of the increase in net income on the time of submission of financial statements is linear regression analysis.The results of this study indicate that the increase in net income does have a significant effect on the time of submission of financial statements, but the relationship of influence between the two is negative. It indicates the companies had increased net profit tend to be longer in delivering their financial statements, because in the financial statement reporting process which generates net income is needed general audit process to ensure that the numbers in the financial statements are accurate and accountable.